A new beta generated Kumaraswamy Marshall-Olkin-G family of distributions with applications - Handique, Laba; Chakraborty, Subrata (Malaysian Journal of Science, 2017)
Unification of the recently introduced Kumaraswamy Marshall-Olkin-G and Beta Marshall-Olkin-G family of distributions is proposed. A number of important statistical and mathematical properties of the family is investigated. A distribution belonging to the proposed family is shown to perform better than the corresponding distribution from the Kumaraswamy Marshall-Olkin-G and Beta Marshall-Olkin-G family of distributions by considering data fitting with three real life data sets. Key words: Exponentiated family, Power Weighted Moments, AIC and K-S test.